Women's Contribution in Society: An Islamic Perspective - Adzima, Fauzan (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2025)
The concept of gender equality in Islam is often misunderstood, either by those who believe that Islam restricts women's roles or by those who demand absolute equality without considering inherent differences. This article explores the active roles of men and women in Islam using a thematic exegesis approach to QS. An-Nisa (4): 32 and QS. At-Taubah (9): 71, based on Fathul Karim Mukhtashar Tafsir. The analysis reveals that Islam emphasizes equality between men and women in faith and rewards for deeds while guiding them to fulfill roles in accordance with Islamic teachings. Women are provided with opportunities to contribute to various aspects of life, including social and da'wah activities, without violating religious principles. This study also identifies challenges in implementing this concept due to the strong influence of patriarchal culture. Therefore, a comprehensive understanding based on authoritative exegesis, along with supportive policies, is necessary to ensure the just implementation of Islamic values.